2023
DOI: 10.3389/fsurg.2023.1159463
|View full text |Cite
|
Sign up to set email alerts
|

Significance of collateral circulation in managing persistent sciatic artery: Two case reports

Abstract: Persistent sciatic artery (PSA) is a rare congenital anomaly considered an embryologic remnant of the internal iliac artery. Traditionally, the classification systems categorized PSA based on the completeness of PSA and superficial femoral artery (SFA) alongside the origin of PSA. The most common class has been known as type 2a in Pillet–Gauffre classification, meaning complete PSA with incomplete SFA. The mainstay of these patients with limb ischemia has been surgical bypass alongside excision or ligation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the patient's congestive heart failure-associated low output syndrome and hypoalbuminemia-induced plasma volume reduction may have adversely affected the peripheral ischemia even after bypass surgery. Yun et al [11] reported two cases where bypass surgery was not required despite distal embolization. In those cases, distal circulation was preserved via the collaterals from the deep and superficial femoral arteries, and there was no risk of recurrent distal embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the patient's congestive heart failure-associated low output syndrome and hypoalbuminemia-induced plasma volume reduction may have adversely affected the peripheral ischemia even after bypass surgery. Yun et al [11] reported two cases where bypass surgery was not required despite distal embolization. In those cases, distal circulation was preserved via the collaterals from the deep and superficial femoral arteries, and there was no risk of recurrent distal embolization.…”
Section: Discussionmentioning
confidence: 99%